Biomarcadores hematológicos e inflamatórios na predição de severidade da Covid-19 - FERREIRA, Alice de Sá Ferreira (2022)
Introduction: COVID-19 is a disease caused by the highly infectious SARS-CoV-2 virus, leading to thousands of infected in a few days. An important finding in patients affected with COVID-19 is the change in hematological parameters and increased serum concentration of inflammatory cytokines, such as interleukin 6 (IL6), especially in severe cases of the disease. This study aimed to characterize hematological and inflammatory parameters in people affected by COVID-19 and to analyze the predicting power of biomarkers for the severity of the disease. Methods: This is a translational study with adult patients, positive for SARS- CoV-2 and living in a region of the Legal Amazon (São Luís/MA) from which sociodemographic data (age, gender, race/color, marital status, place of origin), health (molecular test result for COVID-19, place of hospitalization – infirmary or intensive treatment unit, oxygen saturation, discharge - hospital discharge or death) and laboratory discharge (hcomplete emogram, C Reactive protein - PCR, ferritin. In addition, inflammatory parameters (Neutrophil-Lymphocyte-Lymphocyte Relationship - RNL and Neutrophil- Platelet Relationship - RNP) were performed and the serum concentration of Pro- Inflammatory Cytokines was determined [Interleukin 6 (IL-6), Tumor Necrosis Factor Alpha (TNF-alpha), Interferon Alpha-2 (IFN-alpha 2), Interleukin 12p40 (IL-12p40), Interferon Gamma (IFN-Gamma), Beta Tumor Necrosis Factor (TNF-Beta), Interleukin 18 (IL-18), Interleukin IL-2R alpha (IL-2R alpha) and Interleukin IL-16 (IL-16)]. The participants were divided into a control group and according to the severity of the disease (moderate COVID-19 and severe COVID-19), which was determined by the place of hospitalization (infirmary or ICU) associated with oxygen saturation or need for mechanical ventilation. The data were analyzed using the software statistical program GraphPad Prism version® 8 and IBM SPSS version 24, with significance level of 0.05. Results: The number of total leukocytes (7598.51±3530 versus 13085±7985), neutrophils (5349.18±3565 versus 21910.75±6808), RNL (6.13±6.94 versus 15.86±25.53) and serum CRP concentration (4.47±4.77 versus 8.67±7.72) had higher averages in the group with severe COVID-19, with statistical significance (p<0.05). The values of total leukocytes and neutrophils presented an area under the ROC curve of 0.747 (p<0.05) and 0.777 (p<0.05), respectively. The RNL and PCR showed, respectively, values of areas of 0.722 and 0.700. The predicting power of pro- inflammatory cytokines to differentiate moderate from severe cases in COVID-19, it was also presented in ROC curve models, and IL-6 presented an area under the curve (AUC) of 0.727, with a cutoff point > 0.93, IL-16 presented AUC of 0.740, with a cutoff point > 33.55 and IFN-Alpha2 showed an AUC of 0.727, with cutoff point > 3.06 demonstrating to be good predictors of covid severity. Conclusion: This study demonstrated that laboratory parameters such as the number of total leukocytes, neutrophils, RNL, PCR, as well as pro-inflammatory cytokines IL-6, IL-16 and IFN-Alfa2 can predict the severity of COVID-19 and may thus be laboratory biomaracators of great help in the clinical management of the patient.